Boa-fé objetiva e suas repercussões civis - Silva, Rodrigo Barbosa Oliveira e (2020)
This dissertation aims to present a scientific approach of the institute of good faith without any purpose of exhausting the study of the theme. The objective of good faith is an inexhaustible source of validation and purification of the law, especially to its functions of integration and control. In this sense, its applicability is consolidated in the national legal system with strong doctrinal and jurisprudential positioning. The conclusion points to the applicability of the institute and its developments in all fields, not just to the private law. In addition, objective good faith is responsible for the integration and control of good law, which itself represents the foundation of our nation in having a free, fair and solidary society